Gut microbiota and intervertebral disc degeneration: a bidirectional two-sample Mendelian randomization study - Ziming Geng; Jian Wang; Guangdong Chen; Jianchao Liu; Jie Lan; Zepei Zhang; Jun Miao (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Although previous studies have suggested a close association between gut microbiota (GM) and intervertebral disc degeneration (IVDD), the causal relationship between them remains unclear. Hence, we thoroughly investigate their causal relationship by means of a two-sample Mendelian randomization (MR) study, aiming to determine the impact of gut microbiota on the risk of developing intervertebral disc degeneration. Methods Summary data from genome-wide association studies of GM (the MiBioGen) and IVDD (the FinnGen biobank) have been acquired. The inverse variance weighted (IVW) method was utilized as the primary MR analysis approach. Weighted median, MR-Egger regression, weighted mode, and simple mode were used as supplements. The Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) and MR-Egger regression were performed to assess horizontal pleiotropy. Cochran's Q test evaluated heterogeneity. Leave-one-out sensitivity analysis was further conducted to determine the reliability of the causal relationship. A reverse MR analysis was conducted to assess potential reverse causation. Results We identified nine gut microbial taxa that were causally associated with IVDD (P < 0.05). Following the Benjamini–Hochberg corrected test, the association between the phylum Bacteroidetes and a higher risk of IVDD remained significant (IVW FDR-corrected P = 0.0365). The results of the Cochrane Q test did not indicate heterogeneity (P > 0.05). Additionally, both the MR-Egger intercept test and the MR-PRESSO global test revealed that our results were not influenced by horizontal pleiotropy (P > 0.05). Furthermore, the leave-one-out analysis substantiated the reliability of the causal relationship. In the reverse analysis, no evidence was found to suggest that IVDD has an impact on the gut microbiota. Conclusion Our results validate the potential causal impact of particular GM taxa on IVDD, thus providing fresh insights into the gut microbiota-mediated mechanism of IVDD and laying the groundwork for further research into targeted preventive measures.